Children Empowerment in C.S. Lewis’ novel “The Lion, the Witch and the Wardrobe” - Adi Irma Suryadi; Dariyana Dariyana (CV. Tripe Konsultan, 2022)
This research is aimed to describe Lucy’s thoughts, feelings, and actions in C.S. Lewis’s novel The Lion, the Witch, and the Wardrobe. The problem formulated in the research will be answered based on Lucy’s thoughts, actions, and feelings and then describe it. The main source for this research was C.S. Lewis’s novel The Lion, the Witch, and the Wardrobe. This novel is considered children’s literature. The focus and the data for this research were events in the novel which showed Lucy’s thoughts, feelings, and actions. The data were analyzed by using qualitative content analysis. The instrument was the researcher himself. There are four criteria: credibility, transferability, dependability, and confirmability, which the researcher used in order to make trustworthiness. The findings revealed that Lucy reflected her thoughts through knowledge and ideas, and understanding others’ feelings; her feelings through empathy and unselfishness; and her actions through her bravery and doing a favor for others. Therefore, this novel contains children’s empowerment, which can be categorized as a good novel. Furthermore, children's empowerment is considered an important aspect in children’s stories and it has a great influence to enrich children’s intelligence and emotion in their growing period.